Describing the impact of aphasia on close family members using the ICF framework. (July 2014) - Grawburg, Meghann; Howe, Tami; Worrall, Linda; Scarinci, Nerina
Abstract Purpose: Aphasia is a communication disorder associated with impairments in spoken language, understanding, reading and writing that impacts upon daily activities, participation in society and the quality of life of those with the condition and their family members. Despite existing literature demonstrating the pervasive and significant effects of aphasia on family members, rehabilitation programming, policy and funding are not well developed. The aim of this qualitative study was to describe the impact of aphasia on family members in the context of changes to their functioning and disability using the framework of the International Classification of Functioning, Disability and Health (ICF). Application of ICF concept of disability or "third-party disability" to family members of people with a health condition is discussed. Method: Twenty family members participated in individual in-depth semi-structured interviews. Interviews were analyzed using qualitative content analysis. Research codes generated were subsequently mapped to the ICF. Results: The results of this study showed that family members experienced positive, neutral and/or negative changes to their body functions and activities and participation due to their significant other's aphasia. Moreover, some family members attributed the development of a health condition or exacerbation of an existing health condition to the aphasia. Conclusion: Interpreted within the framework of the ICF, the results of this qualitative study reveal that family members of people with aphasia experience changes to their functioning and disability, known as "third-party functioning and disability", as a consequence of the health condition of a significant other. Implications for Rehabilitation Use of the ICF framework to describe the effects of aphasia on family members may improve rehabilitation programming, policy and funding for family-centred rehabilitation. Aphasia can lead to the development or exacerbation of health conditions (e.g. anxiety) in family members. In ICF terminology, negative changes (e.g. worry, increased duties and financial strain) that family members experience due to aphasia are called third-party disability and may result in impairments, activity limitations and participation restrictions. Similarly, positive changes (e.g. appreciation, learning and increased tolerance) that family members experience may be called third-party functioning and classified with the ICF as changes to their body functioning, activities and participation.